2022
DOI: 10.21512/tw.v23i1.7275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Entrepreneurship Education and Entrepreneurial Motivation on ARO Gapopin’s Student Interest in Entrepreneurship

Abstract: Indonesia has a problem related to entrepreneurship motivation and interest that must be triggered since younger age. The research aimed to determine the effect of entrepreneurship education and entrepreneurial motivation on the entrepreneurial interest of ARO Gapopin students. The population consisted of students of ARO Gapopin. The research applied a quantitative approach through a questionnaire as an instrument for 195 respondents. Data were analyzed using SPSS 16. The findings indicate the importance of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Individuals need to learn the appropriate techniques and explore new opportunities that will provide an advantage in starting their businesses. Those who are passionate and motivated to create independent businesses are likely to learn about market conditions (Stewart et al , 2007), and institutes can play a vital role in providing EE to individuals who are willing to dedicate their time to an independent lifestyle (Thomassen et al , 2019). However, learning initiatives are often associated with individual preferences and choices (Mahto and McDowell, 2018).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals need to learn the appropriate techniques and explore new opportunities that will provide an advantage in starting their businesses. Those who are passionate and motivated to create independent businesses are likely to learn about market conditions (Stewart et al , 2007), and institutes can play a vital role in providing EE to individuals who are willing to dedicate their time to an independent lifestyle (Thomassen et al , 2019). However, learning initiatives are often associated with individual preferences and choices (Mahto and McDowell, 2018).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…However, learning initiatives are often associated with individual preferences and choices (Mahto and McDowell, 2018). Educational institutes, despite their immense efforts, cannot involve individuals in entrepreneurial learning activities who are not motivated or willing to launch local businesses (Tarigan et al , 2022). Moreover, individuals who are motivated and courageous enough to take risks in building such businesses need knowledge and learning platforms to enhance their entrepreneurial skills (Kah et al , 2022).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Entrepreneurial intention shows the effort that arises from a person to carry out this entrepreneurial behavior. This intention is based on three main motivational factors that influence the final behavior (Mahto & McDowell, 2018;Tarigan et al, 2022). Initial attitude refers to whether you like or dislike being an entrepreneur; Subjective norms refer to the perceptions of those closest to them such as family and peers to approve or support entrepreneurial activities being carried out; and Behavioral control refers to perceptions of the ease or difficulty of being an entrepreneur (I.…”
Section: Entrepreneurial Intention Dan Generation Zmentioning
confidence: 99%
“…Research shows that educational institutions as well as faculty members involved in entrepreneurial activities play an important role in developing an entrepreneurial spirit among university students through innovative programs and a research-oriented culture (Cho & Lee, 2018;Ghina et al, 2017;Le & Loan, 2022;Martínez-Gregorio et al, 2021;Piperopoulos & Dimov, 2015). Previous studies have also shown that entrepreneurship education has a positive effect on entrepreneurial intentions (Paray & Kumar, 2020;Passaro et al, 2018;Saoula et al, 2023;Tarigan et al, 2022;Tomy & Pardede, 2020) Entrepreneurial intention is the most important predictor of individual entrepreneurial behavior (Farrukh et al, 2018). Entrepreneurial intention is determined by individual attitudes and attitudes of subjective norms, subjective norms, and perceived behavioral control (Ajzen, 2020;Bird, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, the government provided direct aid to 2.173 business units in Makassar City, and 13.277 MSMEs were recorded, consisting of 5.311 household businesses, 4.647 micro-businesses, and 3.319 medium enterprises. In the meantime, the Office of Cooperatives noted a discrepancy of roughly 2.464 MSMEs and MSEs that did not receive direct financial assistance (Tarigan, Doringin, & Budiana, 2022). The research aims to determine the impact of economic growth in Makassar City on the MSME sector through the use of digital platforms.…”
Section: Introductionmentioning
confidence: 99%